2018
DOI: 10.1016/j.jcma.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional correlation of multiple imaging modalities with focal choroidal excavation

Abstract: Among all image modalities, NIA was the most sensitive tool in area measurement of FCE and peripheral lesion detection. Also, the volume of FCE was associated with subjective distortion and the area was related to complications. Recording the area and volume of FCE could play an important role in monitoring complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In recent years, it has been suggested that male labor is the major source of family support worldwide. It has been proposed that the male population suffers from greater psychological stress and physiologic fatigue, which are etiologies of CSCR [ 24 ]. In addition, as many articles have revealed, the mean age of CSCR onset is approximately 40 years old, which is typically a peak point in an individuals’ economic responsibilities and work commitments in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been suggested that male labor is the major source of family support worldwide. It has been proposed that the male population suffers from greater psychological stress and physiologic fatigue, which are etiologies of CSCR [ 24 ]. In addition, as many articles have revealed, the mean age of CSCR onset is approximately 40 years old, which is typically a peak point in an individuals’ economic responsibilities and work commitments in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher recurrence rates were observed even if patients had received treatment. For example, following spironolactone treatment, a higher recurrence rate of approximately 48% has been noted within 3–6 months after recovery [ 24 ]. Moreover, a 24.5% recurrence rate has also been observed after photodynamic therapy in subjects with chronic CSCR [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding may be incidental on routine examination. 46 , 53 , 54 Subjective disturbances such as metamorphopsia have been reported even in eyes with normal vision. 43 On examination of the fundus, small FCE lesions may not be apparent.…”
Section: Focal Choroidal Excavationmentioning
confidence: 99%
“…A greater length, area and volume of an FCE lesion impart greater risk of associated macular pathology. 53 , 54 Chen et al found that in multimodal imaging of FCE, the most sensitive modality was near-infrared autofluorescence (NIA), with the ability to better image subretinal and choroidal melanin loss in the form of hypoautofluorescence. A greater area of FCE on autofluorescent imaging was shown to be associated with maculopathy such as CNV and CSC.…”
Section: Focal Choroidal Excavationmentioning
confidence: 99%
See 1 more Smart Citation